STRATEGI MENINGKATKAN PRODUKTIVITAS KARYAWAN MELALUI MOTIVASI KERJA DAN PENGEMBANGAN KARIR: STUDI KASUS DI PT. SUMBER ALFARIA TRIJAYA. TBK MEDAN - Gowasa, Amesiani; Syauqi, Teuku Muhammad; Sahputra, Ngatno; Zikri, T M (Bisnis-Net, 2025)
Employee productivity is essential in achieving company goals. This research analyzes the effect of work motivation and career development on employee productivity at PT Sumber Alfaria Trijaya, Tbk Medan. The research uses descriptive quantitative methods with multiple linear regression techniques. The sample consisted of 80 employees, determined by the Slovin formula from a population of 100 people. Data were collected through observation, interviews, and questionnaires. The t-test results show that work motivation has a positive and significant effect on employee productivity (tcount = 8.096), while career development has no significant effect (tcount = 0.524). F test shows that simultaneously, work motivation and career development have a significant effect on employee productivity (Fcount = 35.541, α = 5%). The coefficient of determination (R²) of 46.7% indicates that work motivation and career development variables explain 46.7% of productivity variability, while 53.3% is influenced by other factors such as work discipline, morale, and job transfer